Influencia de la enfermedad periodontal en el control metabólico de pacientes con diabetes mellitus tipo 2: Revisión de la literature - JoãO, Paulo Steffens [UNESP]; Reinke, Stella Maria Glaci [UNESP]; Muñoz, Angel Miguel; dos Santos, Fábio André; Pilatti, Gibson Luiz (My University, 2010)
There may be an interaction between periodontal disease and some systemic diseases such as diabetes mellitus. The objective of this review was to verify, by means of a review of clinical trials, if there is a positive association between periodontal disease and the glycemic control of type 2 diabetes mellitus (DM-2) patients. Eleven articles that fit the study criteria were revised. It was concluded that periodontal disease may influence the metabolic control of DM-2. Additional studies with larger sample sizes and longer follow up are necessary for a better clarification of this issue.
Review on periodontal disease and metabolic control of diabetes mellitus
Keywords: Blood glucose; Diabetes mellitus; Periodontal diseases; Type 2